Congenital muscular dystrophy, cardiomyopathy, and peripheral neuropathy due to merosin deficiency: Peripheral nerve histology of cauda equina - Erika Hissong, M.D; Steven Salvatore, M.D; Kurenai Tanji, M.D., Ph.D; Ehud Lavi, M.D (Elsevier, 2016)
Peripheral neuropathy, white matter abnormalities, and cardiomyopathy are associated findings with merosin-deficient congenital muscular dystrophy. Although characterization of the neuropathy with nerve conduction studies has been well documented, limited research has been able to correlate histopathology with nerve biopsy in humans. Our understanding of the mechanism, described as a demyelinating neuropathy, is mainly derived from mouse model studies. We report a 23-year-old male who succumbed to respiratory failure and ultimately cardiac arrhythmia in the setting of an uncharacterized end stage progressive muscular disease complicated by cardiomyopathy and severe scoliosis. Autopsy revealed extensive muscular atrophy and replacement by fibroadipose tissue throughout the skeletal muscle and myocardium. Immunohistochemical analysis of the muscle biopsy showed a complete loss of merosin. Thus, the cause for both his muscular disease and demyelinating neuropathy was established with the diagnosis of merosin-deficient muscular dystrophy. Nerve biopsy obtained from the cauda equina showed clear evidence of segmental demyelination and remyelination, providing a better understanding of the proximal peripheral nerve histopathological changes in this disease entity.